Pemenuhan Hak Pendidikan Anak Di Masa Pandemi Covid-19 - Marlon Tahapary; Jantje Tjiptabudy; Renny Heronia Nendissa (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Fulfilling children's rights to education is increasingly difficult to achieve, so it is necessary to fulfill children's education rights during the COVID-19 pandemic.Purposes of the Research: Therefore, this writing aims to analyze and discuss the fulfillment of children's education rights during the covid-19 pandemic. Methods of the Research: The research method used is normative juridical. The approach to the problem used is the statutory approach, conceptual approach, sources of legal materials used are primary legal materials and secondary legal materials. Data collection techniques are through literature study and then analyzed through description using the method qualitative.Resul of the Research:  The results of the study show that the fulfillment of children's education rights during the Covid-19 period has not been fulfilled properly. The rights of children's education as regulated in Law Number 23 of 2002 have also not been implemented properly during this covid period. There are no legal consequences arising from the non-fulfillment of children's education rights. For this reason, the fulfillment of children's rights should be in accordance with what has been mandated in the law so that it can guarantee the fulfillment of children's rights so that they can grow, develop, and participate optimally in accordance with human dignity.